2021
DOI: 10.1101/2021.08.25.21262641
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal Trends in Racial and Ethnic Disparities in Multimorbidity Prevalence in the United States, 1999–2018

Abstract: Background: Multimorbidity, an important health indicator, is a contributor to and result of health inequity. We sought to determine if gaps in multimorbidity by race and ethnicity are decreasing over time. Methods: Serial cross-sectional analysis of the National Health Interview Survey, 1999 to 2018. The study included individuals older than 18 years old, categorized by self-reported race, ethnicity, age, and income. The main outcomes were trends in the prevalence of multimorbidity, defined as 2 or more concu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This finding may be explained by persistent racial differences in prevalence and type of underlying health conditions and socioeconomic stressors that could potentially lead to long sleep duration, including multimorbidity profiles (an indicator of multiple concurrent chronic conditions) and unemployment. [39][40][41] Disparities in multimorbidity prevalence and unemployment rates persisted during the study period for Black individuals, 42,43 which could support this explanation. However, further research is needed to understand these patterns and their causes.…”
Section: Discussionmentioning
confidence: 78%
“…This finding may be explained by persistent racial differences in prevalence and type of underlying health conditions and socioeconomic stressors that could potentially lead to long sleep duration, including multimorbidity profiles (an indicator of multiple concurrent chronic conditions) and unemployment. [39][40][41] Disparities in multimorbidity prevalence and unemployment rates persisted during the study period for Black individuals, 42,43 which could support this explanation. However, further research is needed to understand these patterns and their causes.…”
Section: Discussionmentioning
confidence: 78%
“…This finding may be explained by persistent racial differences in prevalence and type of underlying health conditions and socioeconomic stressors that could potentially led to long sleep duration, including multimorbidity profiles (an indicator of multiple concurrent chronic conditions) and unemployment. 39-41 Disparities in multimorbidity prevalence and unemployment rates persisted over the study period for Black individuals, 42,43 which could support this explanation. However, further research is needed to understand these patterns and their causes.…”
Section: Discussionmentioning
confidence: 87%
“…We found that without concerted efforts to reach underserved clientele, our CDSMP participants tended to be limited to older White females of moderate income who are highly educated. It is critical that we employ ways to serve diverse populations because research shows that racial and ethnic minorities and limited-income populations are disproportionately affected by chronic diseases (Caraballo et al, 2022). Keeping CDSMP inviting and relevant to high-need populations are important considerations both now and in the future.…”
Section: Themes and Lessons Learned From Cdsmp Delivery Theme/lesson ...mentioning
confidence: 99%
“…Racial and ethnic health disparities in chronic diseases have been persistent over time. Even though the U.S. government made elimination of health disparities a national priority in 1985, research shows that there has been no significant reduction in the racial/ethnic gap over the past 2 decades (Caraballo et al, 2022). Post-pandemic, expanded use of practical behavioral health strategies is needed to reach and support racially/ethnically diverse families with members living with chronic disease.…”
mentioning
confidence: 99%